Pengaruh Ukuran Perusahaan dan Return on Equity terhadap Earning per Share pada Perusahaan Pertambangan Batubara di BEI, Periode 2019-2022 - Diajeng Reztrianti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Several coal companies have experienced a decline in profitability and solvency. During the period of 2019-2022, the Earnings Per Share (EPS) of coal mining companies listed on the Indonesia Stock Exchange (BEI) underwent fluctuations. It is suspected that factors such as company size and Return on Equity (ROE) may have influenced these variations in EPS. This study aims to determine the relationship between firm size and return on equity on earnings per share in coal mining companies listed on the Stock Exchange. The study reveals that in the case of the 10 coal mining companies listed on the Indonesia Stock Exchange (BEI), both the company size and Return on Equity (ROE) do not significantly contribute to an increase in Earnings Per Share (EPS). It further indicates that the company size itself has no significant impact on EPS. Additionally, the ROE does not promote an increase in EPS for these coal mining companies